Same Same but Different? Gender Politics and (Trans-)National Value Contestation in Europe on Twitter - Stefan Wallaschek; Kavyanjali Kaushik; Monika Verbalyte; Aleksandra Sojka; Giuliana Sorci; Hans-Jörg Trenz; Monika Eigmüller (Politics and Governance, 2022)
The progress achieved in women’s rights and gender equality has become the target of a backlash driven by “anti-gender” activists and right-wing populists across EU member states. To a large extent, this conflict takes place in the digital and social media spheres, illustrating the new mediatized logic of value contestation. Therefore, we ask to what extent are the debates about gender equality on Twitter similar in three European countries, and how do users engage in these debates? We examine these questions by collecting Twitter data around the 2021 International Women’s Day in Germany, Italy, and Poland. First, we show that the debate remains nationally segmented and is predominantly supportive of gender equality. While citizens engage with the gender equality value online, they do so in a prevailingly acclamatory fashion. In contrast, political and societal actors show higher levels of engagement with the value and receive more interactions on Twitter. Our study highlights the relevance of national contexts to the analysis of (transnational) social media debates and the limited political engagement of citizens on Twitter across Europe. We also critically discuss the strengths and weaknesses of a cross-country social media comparison.